Urban Transformations The Spatial Conduct of the Jewish Middle-class in Interwar Łódź, Poland - Kaplan, Ruthie (Mobile Culture Studies. The Journal, 2024)
The Jewish community of Łódź was the second largest community in Poland before the Second World War. Over approximately 100 years, the living area for the Jewish community had spread from a confined district in the first half of the 19th century to a large settlement area in the center of town in the 20th century. This research shows that the Jewish middle-class area of settlement had not only grown but also that its segregation had started to fade. Following the spatial turn in Jewish studies, this paper demonstrates both spatial everyday life in a multicultural city and the relevance of spatial research in Jewish studies. This paper forms part of extensive ongoing research.